MONITORING SISFO PERSEDIAAN BARANG DI SHOP BERBASIS VISUAL BASIC 6.0 MULTIUSER STUDI KASUS DI CIMORY ON THE VALLEY KABUPATEN SEMARANG - Angga Rachmat (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2019)
Sisfo Monitoring of Goods Inventory in Shop Based on Visual Basic 6.0 Multiuser with FIFO method Studin Case in Cimory on the valley Ssemarang Regency is an information system created to overcome the problem of data processing which is still in manual bookkeeping so it takes a long time and results are inaccurate or recap The data does not even have data storage yet undatabase which results in easy data loss. The existing problems can be overcome by making Monitoring of inventory and making data storage information systems more secure and efficient. The design method of monitoring inventory of goods made using the R&D methodology, Flowchat, DFD, ERD and Normalization. The program used to create this application uses the programming language Microsoft Visual Basic 6.0 and MySQL as Database management. The results of this study indicate that the monitoring of inventory of goods applied in Cimory on the valley Semarang Regency can be used to solve data processing problems in the warehouse which include data data collection, data entry of goods, data collection of goods out, data collection of suppliers and customer data collection can make accurate reports , fast and efficient so that reports can be accounted for and the risk of loss of goods will be minimal.